A randomized, open‐label pharmacokinetic trial of tacrolimus extended‐release dosing in obese de novo kidney transplant recipients. Issue 8 (1st July 2019) - Jasiak‐Panek, Natalia M.; Wenzler, Eric; Patel, Shree; Thielke, James J.; Progar, Kristin; Patel, Shitalben; Brandt, Shane; Huang, Yi‐jen; Benedetti, Enrico; West‐Thielke, Patricia M.
Abstract: Purpose: Tacrolimus extended‐release (TAC‐ER; Astagraf XL ® ) is utilized in many immunosuppressive regimens post‐renal transplantation. Current dosing recommendation for the TAC‐ER in renal transplant is 0.15‐0.2 mg/kg/day administered once daily. The purpose of this study was to determine the best method of dosing TAC‐ER in obese renal transplant recipients. Methods: De novo obese kidney transplant recipients were randomized to receive TAC‐ER 0.15 mg/kg/day based on either adjusted body weight (aBW) or ideal body weight (IBW). Post‐transplant patients underwent three pharmacokinetic assessments over 14 days. The primary endpoint was the difference in TAC‐ER exposure (AUC0‐24) in obese patients dosed using aBW compared with IBW. Results: A total of 20 obese renal transplant recipients were randomized to participate in the study (10 aBW and 10 IBW). Results of the primary outcome (AUC0‐24) on Study Day 1, 7, and 14 were not statistically different between the two groups. There was no difference in the number of days to therapeutic trough concentration between the two dosing weights (aBW = 5.1, IBW = 4.9, days; P  = 0.90). Conclusion: In a population of obese renal transplant recipients, comparable trough concentrations and overall exposure in both groups indicate that IBW may be preferred, as less initial drug was needed to attain adequate exposure.